Awakening the Sleeping Giant? The Euro Crisis and EU Issue Voting in Germany - Luca Carrieri (Coordinamento SIBA, 2019)
This article examines the alterations in the forms of electoral contestation that occurred in Germany due to the Euro Crisis. The Great Recession has probably set in motion new windows of opportunity to awake the Sleeping Giant of European integration. Indeed, by increasing their entrepreneurial efforts on the EU issues, the German parties may have rendered this conflict more contentious, changing electoral behavior. To understand the nexus between the Euro Crisis and European integration politicization, this article analyzes the variations of the EU issue entrepreneurship achieved by the German parties between 2010 and 2014. Moreover, this work presents voting models, testing the fluctuations in the levels of EU issue voting. This two-step empirical research seeks to identify whether the Euro Crisis generated new entrepreneurial strategies, realigning the voters along the Pro-/-Anti-European issue dimension in Germany.